THE INVESTIGATION OF THE DEPRESSION LEVELS OF SIBLINGS OF CHILDREN WITH AUTISM - Uzuner, Muhammet Eyup; Kose, Sercan; Aydin, Mensure; YANAR, Şenol; Ates, Betül (Acta Scientiae et Intellectus, 2024)
Individuals with disabled siblings feel differentiated when compared to other families and their own families, and may suppress feelings and thoughts that they can not express. Focusing on their parents to their disabled siblings makes them feel lonely. This situation can cause depression in individuals who have complex feelings and thoughts due to sibling differences. A total of 50 individuals, 29 females and 21 males, voluntarily participated in this research, with at least one autistic sibling who has been living in Istanbul and with whom these siblings have been specially trained. A questionnaire form was used to determine the personal information and socio-demographic characteristics of the individuals with autistic siblings and "Beck Depression Inventory (BDI)" used to determine depression levels of individuals with autistic siblings was administered by face-to-face interview method. The frequency distribution, mean and standard deviation of the obtained data from demographic characteristics and Beck Depression Inventory were determined in SPSS 22 (Statistical Package for Social Sciences) program. The data were tested at a significance level of 0,05. According to Beck depression scale results; gender, age group, educational level, occupation, number of siblings, number of autistic siblings, age group of autistic sibling, gender of autistic sibling; there was no statistically significant difference according to the variables (p>0,05). Additionally, there was a statistically significant difference was found in the depression levels according to the monthly income variable of the participants (p<0,05). When our study findings are interpreted with literature, it is predicted that the sources obtained by determining the levels of stress and depression experienced by the autistic siblings have a limited number and more definite results can be obtained by providing more research on the subject.